Gestational diabetes mellitus diagnosed with single test glucose screening test and its outcome in a tertiary hospital in South India - H., Sunita T.; Desai, Rathnamala M.; Neravi, Asha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: 1) To assess maternal and neonatal outcomes after screening, diagnosing and treating GDM. 2) Role of single test glucose screening test (GST) in diagnosing gestational diabetes mellitus (GDM) in our population. Methods: A one year retrospective study of women diagnosed with and treated for GDM from Jan 2014 to Dec 2014 at SDM medical college and hospital, Dharwad, Karnataka, India. Case records were retrieved to collect data on maternal and neonatal outcome, glycemic control and diabetic management. Single test GST, as per the latest DIPSI guideline was the test used to diagnose GDM i.e. 75 gm of glucose was given to all pregnant women between 24- 34 weeks of pregnancy, irrespective of the last meal and time of the day and after two hours, plasma glucose was estimated. Women with a 2-hr plasma glucose value of >140 mg/ dl were diagnosed to have GDM and were not subjected further for oral glucose tolerance test (OGTT). In women with high risk factors for GDM, the test was performed in the Ist trimester or at their first visit to the hospital. Results: All booked women in the study period underwent GST i.e. we could do universal screening .The incidence of GDM was 4.8%. 147 women were diagnosed to have GDM out of 3050 women screened for GDM. Of the affected women, 74.1% were managed with diet alone and 24.9% received insulin treatment. Good glycemic control improved both maternal and neonatal outcome. Poor glycemic control and presence of preeclampsia were risk factors for maternal and neonatal complications. Conclusions: Single test GST is a patient friendly and effective approach to screen women for GDM especially in high risk ethnic population. Timely and aggressive management helps improve maternal and neonatal outcomes and also decrease the future risk of development of diabetes both in the mother and the fetus.